Analysis of Decisions Related to Child Custody Due to Parental Divorce (Decision Study Number: 75/Pdt.G/2021/Pn Smr) - Rhizka Rivhaldha, Thasya (Riviera Publishing, 2022)
The main purpose of a marriage is to form a family that gets along well and peacefully. However, marriage can also be broken if the husband or wife decides. Furthermore, the determination of child rights can be done based on an agreement that has been agreed upon by the husband or wife or determination through the consideration of a judge. From the results of this analysis, the determination of child custody is regulated in several provisions of Law No. 1 of 1974 on Marriage, and Law No. 35 of 2014 on Child Protection. If in custody of the child there is a dispute then the court will decide with the consideration of the judges in the best interests of the child's growth and development.